Precast Segmental Box Girders Experimental and Analytical Approaches - Mohamed Nazri, Fadzli; Mohd Yusof, Mohd Azrulfitri; Kassem, Moustafa (SpringerBriefs in Applied Sciences and Technology,, 2019)
This book explores the fundamentals of the elastic behaviour of erected precast segmental box girders (SBG) when subjected to static load, as well as the construction process (casting and erection work) involved. It analyzes and compares the experimental results with those obtained using the finite element method and theoretical calculations. A short-term deflection analysis for different loads is obtained by determining the maximum deflection, stress and strain value of single span precast SBG under a variety of transversal slope. The outcome of this work provides a better understanding of the behaviour of precast SBG in terms of structural responses as well as defects, so that maintenance work can then be focused on the critical section at mid span area specifically for the bridge project longitudinally and transversely. The book is of interest to industry professionals involved in conducting static load tests on bridges, and all researchers, designers, and engineers seeking to validate experimental work with numerical and analytical approaches.